Generation of patient-derived pediatric pilocytic astrocytoma in-vitro models using SV40 large T: evaluation of a modeling workflow - Selt, Florian; El Damaty, Ahmed; Schuhmann, Martin U.; Sigaud, Romain; Ecker, Jonas; Sievers, Philipp; Kocher, Daniela; Herold-Mende, Christel; Oehme, Ina; Deimling, Andreas von; Pfister, Stefan; Sahm, Felix; et al. (Journal of neuro-oncology, 2023)
Although pediatric low-grade gliomas (pLGG) are the most common pediatric brain tumors, patient-derived cell lines reflecting pLGG biology in culture are scarce. This also applies to the most common pLGG subtype pilocytic astrocytoma (PA). Conventional cell culture approaches adapted from higher-grade tumors fail in PA due to oncogene-induced senescence (OIS) driving tumor cells into arrest. Here, we describe a PA modeling workflow using the Simian Virus large T antigen (SV40-TAg) to circumvent OIS.
Gesehen am 22.01.2024